Temperature and number evolution of cold cesium atoms inside a wall-coated glass cell - 黄家强 张建伟 王时光 王正博 王力军 (Chinese physics B, 2015)
We report an experimental study on the temperature and number evolution of cold cesium atoms diffusively cooled inside a wall-coated glass cell by measuring the absorption profile of the 62S1/2 （F = 4） →62P3/2（F= 5） transition line with a weak probe laser in the evolution process. We found that the temperature of the cold atoms first gradually decreases from 16 mK to 9 mK, and then rapidly increases. The number of cold atoms first declines slowly from 2.1 × 109 to 3.7×108 and then falls drastically. A theoretical model for the number evolution is built and includes the instantaneous temperature of the cold atoms and a fraction p, which represents the part of cold cesium atoms elastically reflected by the coated cell wall. The theory is overall in good agreement with the experimental result, and a nonzero value is obtained for the fraction p, which indicates that the cold cesium atoms are not all heated to the ambient temperature by a single collision with the coated cell wall. These results can provide helpful insight for precision measurements based on diffuse laser cooling.